Deconstructing section 25 of the Constitution: has the inclusion of property rights in section 25 of the Constitution helped or hindered the transformation purpose of the Constitution, and specifically the state's commitment to land reform? - Basajjasubi, Allan Nsubuga (Department of Public Law, 2017)
Prior to the advent of the Constitution and constitutional democracy land policies of the apartheid state secured resource ownership and control of land exclusively for the white minority, whilst dispossessing large communities of black, coloured and Asian people and banishing them to designated "native reserves". Shortly before the transition to democracy liberation groups together with the old apartheid regime, sought to negotiate on land policies which not only constitutionalized property rights but which also constitutionalized a priority to land reform in order to redress the injustices of the past. This paper examines whether the law, as captured in s 25 of the bill of rights, stood in the way of government inn unfolding a progressive programme of land reform. As a contribution to the debate surrounding issues on the appropriateness of the expropriation of land as a means of accelerating the pace of land reform, this papers offers a critical lens through which the state's current land reform policies are evaluated against the Constitution's transformative agenda of facilitating for an equitable system of land rights that provide development opportunities for black and coloured South Africans. Through an analysis of constitutional jurisprudence-including academic literature and legislation- this paper aims to investigate whether section 25 by reason of a lacking of sufficient expropriation and redistribution, as mechanisms for accelerating land reform, is anti-transformation. By deconstructing section 25 (the property clause) my paper offers insight into the controversial and rebuttable presumption that it is in fact not the Constitution but the state, that is responsible for frustrating and impeding the pace of transformation via constitutionally permissible land reform.